2021
DOI: 10.1186/s12917-020-02720-w
|View full text |Cite|
|
Sign up to set email alerts
|

Gastrointestinal ultrasonographic findings in cats with Feline panleukopenia: a case series

Abstract: Background Feline panleukopenia virus (FPV) is very resistant and highly contagious and infects domestic cats and other felids. FPV is particularly widespread among sheltered cats, and is associated with high morbidity and mortality, causing severe gastroenteritis characterized by anorexia, lethargy, fever, dehydration, hemorrhagic diarrhea, and vomiting. There is currently no data on the ultrasonographic features of cats affected with FPV. This case series describes abdominal ultrasonographic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, only two cats in close contact with parvovirus-infected animal tested antigen and PCR positive. The mortality rate in our study was 8.69% (2/23), which is a significantly lower rate than that in other studies, where it ranged from 50% to 90% ( 6 , 8 , 19 ). Sequencing of positive samples and their subsequent BLASTn analysis excluded CPV-2 infection and confirmed the presence of FPV.…”
Section: Discussioncontrasting
confidence: 81%
“…On the other hand, only two cats in close contact with parvovirus-infected animal tested antigen and PCR positive. The mortality rate in our study was 8.69% (2/23), which is a significantly lower rate than that in other studies, where it ranged from 50% to 90% ( 6 , 8 , 19 ). Sequencing of positive samples and their subsequent BLASTn analysis excluded CPV-2 infection and confirmed the presence of FPV.…”
Section: Discussioncontrasting
confidence: 81%
“…In particular, FPV generally causes mild symptomatic or asymptomatic infection in most mature cats. However, FPV excretion in swabs from infected mature cats may cause a variety of potentially severe infections for newborn cats, even life-threatening ( Isaya et al 2021 ). Thus, a faster, simpler, and more cost-effective detection method for FPV has become increasingly significant to protect vulnerable and high-risk cats, especially in resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FPV mainly replicates in small intestinal crypt cells and lymphoid cells ( 43 ). Replication often leads to bleeding in the small intestine and stomach, which is the main cause of hemorrhagic diarrhea in cats ( 41 ).…”
Section: Discussionmentioning
confidence: 99%